Improving efficacy of cancer immunotherapy through targeting of macrophages - Elisa Peranzoni; Emmanuel Donnadieu (Taylor & Francis Group, 2019)
T cell-based immunotherapies have revolutionized the treatment against cancer. But complete and long-lasting efficacy is only observed in a fraction of the patient population. One of the suspected causes is the inability of cytotoxic T cells, endowed with tumor killing ability, to reach their malignant targets. Using dynamic fluorescence imaging to study the dynamic of T cells in tumors from patients with lung cancer, we have recently demonstrated that macrophages trap the T lymphocytes, which are not longer able to contact the tumor cells. In murine models of breast cancer, we could show that the depletion of macrophages allows T cells to interact with tumor cells, a process which enhances anti-PD-1 immunotherapy. These findings illustrate the relevance of current clinical trials combining a strategy that deplete or modulate macrophages with anti-PD-1 immunotherapy.